PENGARUH EDUKASI TERHADAP PENGETAHUAN GENERASI MUDA DI MEDIA SOSIAL TERKAIT PERAN ESSENTIAL OIL SEBAGAI UPAYA PREVENTIF COVID-19 - Abdul Rahem; Althaf Azhar Nur Fadhilah; Fatimah Azwa; Anggie Rahajeng Kusumastuti; Clara Ayu Noventia Pradjarto; Gerindra Heksa Alvianto; Luh Putu Ayu Teresnaning Devi; Naura Reva Anjani; Restu Dhimas Prayoga; Retno Intan Avina Rahmawati; Salsabillah Amalia Furtina; Septian Aslam Pratama; Tasya Sherina Hendra Febyola; Wuri Kasih Jayendrati; Zalza Billa Arosa (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2022)
Due to the COVID-19 pandemic, there has been an increase in sales and purchases of essential oils. This trend happens because essential oils are claimed to be beneficial for COVID-19 treatment despite there has been no scientific evidence to support this claim. To discover and increase public knowledge regarding the role of essential oils as an effort to prevent the COVID-19 virus, education was provided through social media. The research method used is a quasi-experimental research method or a quasi-experimental type of one group pretest and posttest design. In this study, the targeted respondents are the young generation aged 18-30 years who live on Java. Respondents answered questions using google form to find out the increase in knowledge of the younger generation before and after providing education regarding the role of essential oils. The instrument used is a google form test before and after presenting education related to the role of essential oils. Based on the research, the majority of the younger generation already knows enough information about essential oils in general.